Commentaries on "Evaluating the Geographic in GIS". Issue 3 (17th July 2019) - Warren, Stacy; Harris, Trevor; Goodchild, Michael; Solís, Patricia
Abstract: In this article, four geographers who are also GIS practitioners critique "Evaluating the Geographic in GIS." Sparked by the arguments in that article, they pose fundamental questions about how geography can best contribute to GIS practices.